CHALLENGES IN PHRASEOLOGY: AN ESL STUDY AT SPACE UTM - Ali, Fariha Diyana Awang; Zaimi, Farah Hamizah Muhd; Bakhri, Nur Hazirah Mohd; Nazri, Nurnadirah Shahira; Zakaria, Nur Liyana; Handeri, Azhan Zulfadhli (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates the phraseological challenges faced by English as a Second Language (ESL) learners in academic writing at SPACE UTM. Despite ongoing efforts to enhance English proficiency in Malaysia, students continue to struggle with the accurate use of collocations, idiomatic expressions, and syntactically natural constructions, which significantly affect the clarity and fluency of their writing. The research aims to identify the most frequent phraseological errors and uncover the underlying factors contributing to these issues. Adopting a qualitative approach, the study analyzed academic writing samples and responses to structured questionnaires from ten ESL foundation-level learners. Content and thematic analysis revealed that the most common errors included incorrect phrasing, verb form inconsistencies, redundant expressions, and sentence fragments. These issues were linked to first language interference, limited exposure to authentic academic phraseology, and insufficient instruction in fixed expressions. The findings highlight the need for more targeted pedagogical interventions, including explicit teaching of collocational patterns, integration of academic phrase banks, and structured self-editing strategies. By addressing these areas, educators can significantly enhance students’ academic writing proficiency and prepare them for more effective communication in higher education and professional contexts.